Analisa Strategi Peningkatan Daya Saing Sekolah Berbasis Pondok Pesantren Melalui Inovasi Manjemen Pendidikan di Kabupaten Pringsewu - Lukman Hakim; Susanto Susanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Education is a major pillar in the development of the nation and civilization, education that aims to form human resources that are intellectually superior. In Indonesia, the existence of private schools integrated with the Islamic boarding school system (Pon Pes) has long been an integral part of the national education system. This study uses a qualitative approach with a multi-site case study type that aims to analyze in depth the strategy of increasing the competitiveness of private schools based on Islamic boarding schools through educational management innovation. The study was conducted at five private schools based on NU Islamic Boarding Schools spread across various sub-districts, with the research time adjusted to the process of collecting field data in stages until data saturation is reached. Based on the research results and discussion, it can be concluded that educational management innovation in private Islamic boarding schools plays a significant role in increasing institutional competitiveness in the era of globalization. The developed strategy model includes the integration of Islamic boarding school values ​​and modern management, collaborative leadership, an adaptive curriculum, human resource development, and the use of technology based on Islamic values.Theoretical and Practical Implications This research provides theoretical contributions to the development of Islamic education management studies as well as practical implications for Islamic boarding school managers.